Stock Market's Reactions to Revelation of Tax Evasion: An Empirical Assessment - Andreas Brunhart (Swiss Journal of Economics and Statistics, 2014)
Additionally to the financial crisis causing a world recession, Liechtenstein's financial sector has been challenged by the so-called "Zumwinkel-Affair", when a whistle-blower sold data of hundreds of tax evaders to international tax authorities. This paper investigates the impact of this affair on the daily stock prices of banks from Liechtenstein. An unconventional augmented GARCH-model (labelled as "augmented amalGARCH"), which outperforms conventional models, is introduced and dynamically analyses various influences on risk and returns. Also, an event study framework is applied. The main finding beyond further conclusions is that the Zumwinkel-Affair had an (accumulating) effect on risk, but surprisingly no impact on average stock return could be detected.
Keywords: C01; C22; G01; G21; 330; Tax evasion; Liechtenstein; financial institutions; stock price volatility; augmented GARCH; amalGARCH